A note on flow-induced force measurement of oscillating cylinder by loadcell. (1st February 2022) - Alam, Md. Mahbub
Abstract: The paper presents a systematic understanding of the importance of the quiescent-fluid added mass consideration in the estimation of loadcell-measured fluid force acting an oscillating cylinder. The output of the loadcell of a cylinder oscillating in quiescent fluid captures the cylinder inertia, added mass inertia, and fluid damping forces. When a cylinder-loadcell system undergoes flow-induced vibrations, the loadcell captures flow-induced fluid forces on the cylinder, the cylinder inertia, the quiescent-fluid added mass inertia, and the quiescent-fluid added damping force. To correctly estimate the flow-induced force on the oscillating cylinder, the cylinder inertia, quiescent-fluid added mass inertia, and quiescent-fluid added damping forces have to be subtracted from the loadcell output . To approximate flow-induced force using a loadcell, quiescent-fluid added mass inertia and quiescent-fluid added damping forces have not been considered in the literature while the former has a great contribution to the loadcell output. If the quiescent-fluid added mass inertia is not considered, the phase relationship between the response and estimated force may not be consistent but defers depending on the quiescent-fluid added mass. The present systematic analysis of forces and added mass would be handy for postgraduate studies, researchers, and engineers. Highlights: A systematic understanding of significance of quiescent-fluid added mass is presented. Loadcell captures fluid forces, cylinder inertia, added mass inertia and added damping force. Cylinder inertia, added mass inertia, and added damping forces have to be subtracted from loadcell output. Added mass inertia has to be considered to correctly obtain the phase between response and force.